Analysis of traffic and industrial source contributions to ambient air pollution with nitrogen dioxide in two urban areas in Romania. (January 2019) - Paraschiv, Spiru; Paraschiv, Lizica-Simona
Abstract: The main purpose of this study is to investigate NO2 temporal distribution in two urban areas in Romania based on data measured by stationary monitoring stations during 2016 and 2017. Analysis of the measurement data show that NO2 emissions from traffic type sources has a higher contribution to the urban pollution than industry type source. The analysis of emission trend in the two cities (for 2 years), shows an effective reduction in emissions from industrial type source but an increase in emissions from traffic type source with 12.88 to 28.45 %.